Application of innovative tools for effective management of development projects in modern conditions - ZYAKHOR, Dmitry; MOLODKO, Oleksii (Ways to Improve Construction Efficiency, 2025)
The purpose of this study was to consider certain tools for increasing the efficiency of management of investment and development projects and develop practical prerequisites for increasing the performance of construction projects. The main approaches to this study include the use of flexible methods, the use of principles of system analysis for the management of development projects, including innovative technologies, among which Agile, Lean, BIM occupy a significant place. Leading innovations in development project management have been the introduction of Building Information Modeling (BIM), Design for Manufacturing and Assembly (DfMA), Agile, Lean and 3D printing. Such digital technologies have significantly transformed approaches to development projects, offering more integrated and visualized management of construction processes. A digital integrated platform uses digital building models that contain accurate geometric and technical data about all elements of the structure, which allows all project participants, from architects and engineers to builders and customers, to work together on a single information platform. This contributes to better planning, coordination, forecasting of results, cost optimization, as well as effective resource management at all stages of construction. Thanks to the use of this technology, it is possible not only to reduce the number of errors at the stage of physical implementation of projects, but also to significantly reduce the time and costs associated with construction. Modern innovative and digital tools are not only a technology, but also a strategic tool that allows development companies to approach construction innovatively, while ensuring high return on investment and meeting customer needs. The use of certain digital tools in the management of existing construction projects also contributes to the globalization of the construction services market, allowing companies to easily adapt to international projects and standards, which is a great advantage in the face of constantly increasing competition.